(untitled) (Research, Society and Development, 2023)
Objective: Conduct a systematic review on the use of Laser Therapy in cases of Temporomandibular Disorders. method: A literature review was carried out, using articles from the PubMed, Lilacs and Scielo databases, which aimed to perform speech therapy with Laser Therapy in TMD cases, published in Portuguese, between 2016 and 2021 with the descriptors “laser therapy”, “temporomandibular disorder” and “speech therapy”. Articles published in a period shorter than the pre-established period, which performed laser therapy in the treatment of other pathologies and which did not describe the use of laser therapy as a resource for the treatment of TMD, were excluded. results: After screening, 12 articles were selected, in which the results showed that the LASER is effective in controlling painful temporomandibular disorders, enabling a reduction in pain intensity and mandibular movement, and an improvement in the quality of life of these patients can also be observed. individuals. conclusion: It is concluded that the use of Laser Therapy is considered effective for the treatment of TMD cases, as through the studies presented in this work, it was concluded that when associated with myofunctional therapy, this resource brings several benefits to the individual, such as decreased pain, improved mouth opening, balance of stomatognathic system functions and improved quality of life.